Implementation of a process-orientated multidisciplinary approach (POMA), a system of cost-effective healthcare delivery within a cardiac surgical unit. Issue 6 (8th December 2008) - O'Regan, D; Shah, S; Mirsadraee, S; Al-Ruzzeh, S; Karthik, S; Jarvis, M
Abstract : Background: The process-orientated multidisciplinary approach (POMA) is a means of delivering consultant-led healthcare from the first outpatient clinic visit through to discharge, bringing together clinical and operational management that can result in effective resource utilisation and improved patient care. Methods: Prospectively collected data from patients undergoing primary isolated coronary artery bypass graft (CABG) were collected before and after the application of POMA (246 and 260 patients, respectively). The impact of POMA was analysed on the number of cancellations (NOC), postoperative clinical incidents (POCI), postoperative length of stay (PLOS) and cost in the practice of one consultant surgeon. Data were obtained from our clinical database (PATS—Dendrite), which is used risk stratify patients and prospectively to collect clinical/operative data and outcomes. Results: Patients were matched for all variables except for the European Cardiac Surgical Risk Score (EuroSCORE) which was 1.93 for pre-POMA patients and 2.73 for post-POMA patients (p<0.05). Cancellations significantly decreased from 4.5% (n = 11, pre-POMA) to 0.4% (n = 1, post-POMA) (p<0.05). POCI significantly decreased from 44.3% (n = 109, pre-POMA) to 36.2% (n = 94, post-POMA) (p<0.05). PLOS significantly decreased from 6.3 (pre-POMA) to 6.1 days (post-POMA) (p = 0.002). Regression analysis showed that implementation of POMA was the only significant factor in the reduction of POCI and PLOS (p<0.05). POMA resulted in an overall saving of £285 868 (€400, 215; US$508, 845) calculated using the 2005 National Health Service (NHS) tariffs. Conclusions: The implementation of POMA was the only significant known (or measured) factor that improved the operational efficiency and clinical outcome of a single surgeon's practice. The authors believe the principles deserve to be studied further to see if the results can be replicated.